2016
DOI: 10.1039/c5ra27375g
|View full text |Cite
|
Sign up to set email alerts
|

High-performance capacitive behavior of layered reduced graphene oxide and polyindole nanocomposite materials

Abstract: PIn/RGO nanocomposite prepared by in stiu chemical polymerization shows specific capacitance of 322.8 F g−1 at 1.0 A g−1, good stability of 94.5% retention after 1000 cycles, and high energy density of 36 W h kg−1 at high power density of 5000 W kg−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 50 publications
2
39
1
Order By: Relevance
“…All the composites showed that the graphenebased materials were covered with PIn because indole monomers can adsorb and grow on the surfaces of graphene-based materials. 40 For example, this phenomenon is illustrated in Fig. 1(d) and (e), which show the surface morphologies of cm-GO and the in situ cm-GO/dPIn composite, respectively.…”
Section: Characterizationmentioning
confidence: 88%
See 1 more Smart Citation
“…All the composites showed that the graphenebased materials were covered with PIn because indole monomers can adsorb and grow on the surfaces of graphene-based materials. 40 For example, this phenomenon is illustrated in Fig. 1(d) and (e), which show the surface morphologies of cm-GO and the in situ cm-GO/dPIn composite, respectively.…”
Section: Characterizationmentioning
confidence: 88%
“…Furthermore, PIn-composited graphene based materials can be applied in various electronic applications; for example, GO/PIn composite was utilized as a supercapacitor, 36 GO/PInincorporated Ag was applied as an electrode material, 39 and rGO/PIn nanocomposite was used as a capacitor. 40 However, graphene-based material/PIn composites have not been previously reported in sensor applications.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, polyindole (PIn) has attracted significant interest due to its superior thermal stability, high redox activity, and tunable electrical conductivity . It has been reported that PIn has higher thermal stability than PANI, PPy, and polythiophene.…”
Section: Introductionmentioning
confidence: 99%
“…and tunable electrical conductivity. 19 It has been reported that PIn has higher thermal stability than PANI, PPy, and polythiophene. This high thermal property can have a positive effect to the ER fluid application since the applications mentioned above can be used in a broad temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the spectrum of PIn as shown in Fig. 3(c) displays the vibration at 734 cm −1 corresponding to the presence of C-H bond in the benzene ring of indole, the vibration at 1104 cm −1 due to stretching of C-N bond, whereas the bands at 1222 cm −1 and 1430 cm −1 are characteristics of the aromatic ring stretch vibrations in PIn 42 . It is to be noted that the spectrum of ZnO/PIn-MWCNTs nanocomposite given in Fig.…”
Section: Resultsmentioning
confidence: 99%